2017
DOI: 10.1038/nrc.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary perspective on field cancerization

Abstract: Tumorigenesis begins long before the growth of a clinically detectable lesion and, indeed, even before any of the usual morphological correlates of pre-malignancy are recognizable. Field cancerization, which is the replacement of the normal cell population by a cancer-primed cell population that may show no morphological change, is now recognized to underlie the development of many types of cancer, including the common carcinomas of the lung, colon, skin, prostate and bladder. Field cancerization is the conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
332
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(346 citation statements)
references
References 188 publications
9
332
0
5
Order By: Relevance
“…Aberrant DNA methylation is known to be accumulated in non‐cancerous or precancerous tissues exposed to environmental factors, producing an “epigenetic field for cancerization” . The level of epigenetic field for cancerization is a promising cancer risk marker, as evidenced by the multicenter prospective cohort study for metachronous gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant DNA methylation is known to be accumulated in non‐cancerous or precancerous tissues exposed to environmental factors, producing an “epigenetic field for cancerization” . The level of epigenetic field for cancerization is a promising cancer risk marker, as evidenced by the multicenter prospective cohort study for metachronous gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…41 Aberrant DNA methylation is known to be accumulated in noncancerous or precancerous tissues exposed to environmental factors, producing an "epigenetic field for cancerization". 45,46 The level of epigenetic field for cancerization is a promising cancer risk marker, as evidenced by the multicenter prospective cohort study for metachronous gastric cancer. 47,48 The present study also supported that this epigenetic marker is well associated with tumor development, and indicated that it is useful to monitor the effect of modulation of the intestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, tumour diagnosis has focused on histological and molecular features, yet it is well known that the surrounding cells and other areas of the tissue may display premalignant histological changes such as dysplasia; furthermore, many genetic alterations occur without cytological changes. These environmental changes can affect tumour progression by exerting evolutionary pressure on tumour cells and ultimately determining which mutations are selected . Examples of preneoplastic histological lesions include dysplasia (cytological atypia, large hyperchromatic nuclei or nucleoli) and in‐situ carcinomas (with no basement membrane invasion), which are observed in most carcinomas.…”
Section: Problems and Barriersmentioning
confidence: 99%
“…It is noteworthy that some early neoplastic lesions such as colon adenomas and skin naevi are polyclonal. Progression to cancer probably involves the accumulation of multiple field cancerisation driver mutations among synergistically acting groups of mutations . In this regard, molecular studies of peritumour areas in normal ducts of the breast or prostate may show a high number of genetic alterations and driver mutations .…”
Section: Problems and Barriersmentioning
confidence: 99%
“…It seems likely, based on these observations, that regressed AK skin is not the same as nonsun‐exposed skin, and is potentially more prone to recurrence and hence also to progression to SCC. It may additionally reflect that AKs are arising in a region of the skin that carries some but not all of the phenotypes required for malignancy in a process called field cancerization . This work paves the way for a comprehensive analysis of gene expression changes in AK regression and persistence and in field cancerization, enabling the discovery of more targeted therapies at multiple stages during epidermal neoplasia and SCC progression.…”
mentioning
confidence: 98%